mTORC1 and PKB/Akt control the muscle response to denervation by regulating autophagy and HDAC4 - Perrine Castets; Nathalie Rion; Marine Théodore; Denis Falcetta; Shuo Lin; Markus Reischl; Franziska Wild; Laurent Guérard; Christopher Eickhorst; Marielle Brockhoff; Maitea Guridi; Chikwendu Ibebunjo; et al. (Nature Communications, 2019)
Denervation leads to muscle atrophy and neuromuscular endplate remodeling. Here, the authors show that a balanced activation of mTORC1 contributes to the dynamic regulation of autophagic flux in denervated muscle and that activation of PKB/Akt promotes the nuclear import of HDAC4, which is essential for endplate maintenance upon nerve injury